A EDUCAÇÃO RURAL NO BRASIL E NO PARANÁ NOS ANOS 50 E A MATERIALIZAÇÃO NO CURSO NORMAL REGIONAL DE GUARAPUAVA - Palhano, Isabel Castilho (2014)
Current dissertation historicizes the Brazilian aftermath of World War II, the context of world re-organization of the great capitalist countries. It was the period in which liberal discourse of the universality of human rights brought to the fore education as one of the priorities in the requirements of the capitalist world. The discourse of modernization in Brazil blamed education in the rural areas and attributed responsibilities so that economical backwardness could bevanquished. The establishment of specific programs and courses were specifically undertaken. Current research analyzes the contradictions within teachers` formation for teachers working in the rural milieu in the 1950s through the ideology foregrounding the school curriculum. The 1945-1964 historical period evidences not merely the contradictions within the educational context but also those in the economical, political and social fields, with special emphasis of the undertaking of State policies oriented by international organizations` premeditated intervention. How were these policies undertaken within the national, state and municipal level in Guarapuava PR Brazil? What were the philosophical and ideological ideas that underpinned teaching reforms by the Regional Teachers` Training Course? The analysis of documents that underpinned the suggestions of teacher formation courses in the 1950s is undertaken at the national and state levels to answer the above issues. Specific theory, class diaries of the Colégio Belém in Guarapuava, articles in the newspapers of the period, governors` messages and reports have also been employed. It will be shown that, in the wake of the modernizing discourse, Brazil dons the nationaldevelopmentalism generating demands for educational change. However, the contradiction of the coexistence of cognitive psychology and encyclopedia pedagogy (concentrated on memory) becomes evident among the progress and disruption of the changes. In fact, New School contents are given priority together with conservationist methodologies. What occurs in Guarapuava is a reflection of the ideas of pedagogical thought worked out for Brazil and Paraná. On the other hand, within the contradictions present in rural education, factors emerged which were part and parcel of the peasant class such as literacy, schooling and the rise of trade unions. The development period was refurbished contradictorially towards a `centerperiphery`-dependent capitalism which whetted exploitation and the degradation of work as a human product.